PRICING OF THE ASIAN OPTION WITH THE KAMRAD-RITCHKEN’S TRINOMIAL MODEL - Nabila Wafa’, Jihan; Siswanah, Emy (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Asian Option determines its payoff option value by the average stock during the option period. This research aims to determine the price of Asian Option by average arithmetic using Kamrad-Ritchken’s Trinomial method. The Kamrad-Ritchken trinomial model is one of the models in the trinomial method used to determine the option value that provides a procedure for determining the barrier parameter or stock price tendency ( ). The stock price tendency makes the trinomial model right on the dotted line of possible stock prices. This study is different from previous studies because the focus of this study is to determine the price of Asian options, both call options and put options with different maturity time variables. The data used for this research are taken from the NVIDIA Corporation (NVDA) data from August 2nd, 2021 – September 29th, 2023. Next, several parameters of option value are determined, which are the initial stock price ( ), contract price ( ), risk-free interest rate ( ), period ( ), stock return ( ), variance ( ), volatility ( ), stock price trend ( ), stock price increase ( ), stock price decrease ( ), stock price increase opportunity ( ), fixed stock price opportunity ( ), stock price decrease opportunity ( ), and barrier ( ). These parameters are used to calculate the price of Asian Option. According to the calculation result by average arithmetic using Kamrad Ritchken’s Trinomial method, the longer the maturity date of an option, the more expensive the option price will be.